2012
DOI: 10.1038/ajg.2012.6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Esophageal Eosinophilia Varies by Climate Zone in the United States

Abstract: Objectives The epidemiology of eosinophilic esophagitis (EoE) is rapidly evolving, and differences in climate could impact the prevalence of EoE. We aimed to examine the association between esophageal eosinophilia and climate zones in the U.S. Methods This was a cross-sectional study of esophageal biopsies from 2008 to 2010 in a large U.S. pathology database. Cases were patients with esophageal eosinophilia; controls had normal esophageal biopsies. A Köppen-Geiger (K-G) climate class was assigned to each pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 48 publications
4
67
0
1
Order By: Relevance
“…This is further supported by the observation that EoE varies by climate zones in the USA [63]. A confirmation of a seasonal dependency of EoE would be an indicator that external seasonal factors (especially pollen) could play a substantial role in the pathogenesis of this Th2-type inflammation.…”
Section: Eoe and Seasonal Distributionsupporting
confidence: 57%
“…This is further supported by the observation that EoE varies by climate zones in the USA [63]. A confirmation of a seasonal dependency of EoE would be an indicator that external seasonal factors (especially pollen) could play a substantial role in the pathogenesis of this Th2-type inflammation.…”
Section: Eoe and Seasonal Distributionsupporting
confidence: 57%
“…26,27 Given the similarity in geographic locale to Olmsted County, Minnesota, and thus the likelihood that environmental factors would be relatively similar, we had postulated that our results would be supportive of previous findings. 17 Hurrel et al 28 had demonstrated that EoO has the highest prevalence in the cold and arid zones. However, unlike these studies conducted in the similar climate environments, we did not find an increased monthly or seasonal incidence in our population.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 There is seasonal and geographic variation in frequency, with higher rates reported in the summer and early fall 22 and in cold and arid zones. 27 These temporal and geographic trends likely represent the putative atopic etiology of EoE.…”
Section: Demographicsmentioning
confidence: 99%